PENGARUH PENGENDALIAN INTERNAL PERSEDIAAN BAHAN BAKU DAN PERENCANAAN PROSES PRODUKSI TERHADAP KELANCARAN PROSES PRODUKSI PADA PT. ADE TEXTILE INDUSTRIES (ADETEX) - Achmad Fathony, Aditya; Maesaroh, Sinta (Fakultas Ekonomi UNIBBA, 2025)
This study analyzes the influence of Internal Control of Raw Material Inventory and Production Process Planning on the Smoothness of the Production Process at PT Ade Textile Industries (Adetex). The analytical method used in this study is descriptive analysis with a quantitative approach, and the population consists of all employees of PT Ade Textile Industries (Adetex). The sampling technique applied is disproportionate stratified random sampling. The data analysis method employed is multiple linear regression analysis, using the SPSS version 20 software. The results of the study indicate that, partially, internal control of raw material inventory has a positive and significant influence on the smoothness of the production process. Likewise, production process planning also has a positive and significant influence on the smoothness of the production process. Simultaneously, there is a significant influence of internal control of raw material inventory and production process planning on the smoothness of the production process at PT Ade Textile Industries (Adetex).